2020
DOI: 10.7554/elife.53552
|View full text |Cite
|
Sign up to set email alerts
|

Separable gain control of ongoing and evoked activity in the visual cortex by serotonergic input

Abstract: Controlling gain of cortical activity is essential to modulate weights between internal ongoing communication and external sensory drive. Here, we show that serotonergic input has separable suppressive effects on the gain of ongoing and evoked visual activity. We combined optogenetic stimulation of the dorsal raphe nucleus (DRN) with wide-field calcium imaging, extracellular recordings, and iontophoresis of serotonin (5-HT) receptor antagonists in the mouse visual cortex. 5-HT1A receptors promote divisive supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 139 publications
5
38
0
Order By: Relevance
“…ON-OFF contrast asymmetries are likely to be inherited in part from the retina ( Cooper, 2016 ; Kremkow et al, 2014 ) and may depend on parameters that we did not investigate such as spatial frequency ( Jansen et al, 2019 ; Kremkow et al, 2014 ; Onat et al, 2011 ), visual eccentricity, and brain state ( Azimi et al, 2020 ). There is increasingly stronger evidence that ON and OFF pathways remain cortically segregated ( Kremkow and Alonso, 2018 ) and operate relatively independently.…”
Section: Discussionmentioning
confidence: 99%
“…ON-OFF contrast asymmetries are likely to be inherited in part from the retina ( Cooper, 2016 ; Kremkow et al, 2014 ) and may depend on parameters that we did not investigate such as spatial frequency ( Jansen et al, 2019 ; Kremkow et al, 2014 ; Onat et al, 2011 ), visual eccentricity, and brain state ( Azimi et al, 2020 ). There is increasingly stronger evidence that ON and OFF pathways remain cortically segregated ( Kremkow and Alonso, 2018 ) and operate relatively independently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the computational relevance of activity on this timescale, serotonin neuron firing rate changes may be optimized for the nervous system to implement these computational goals. Slow changes in serotonin neuron activity could enable gating or gain control mechanisms (Shimegi et al, 2016;Azimi et al, 2020), bidirectional modulation of relevant inputs and outputs (Avesar and Gulledge, 2012;Stephens et al, 2014Stephens et al, , 2018, or other previously-observed circuit mechanisms that modulate how new information is incorporated (Marder, 2012) to drive flexible behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The serotonergic system plays a key role in the balancing between endogenous and exogenous information involved in the construction of conscious experience, as the perturbation by psychedelic molecules such as DMT shows. This balancing is heavily mediated by the interplay between 5-HT1A and 5-HT2A receptors ( Nichols 2016 ; Azimi et al 2020 ). Although serotonin receptors can be found across the cortex ( Beliveau et al 2017 ), specific mechanisms (at different spatial scales) underlie the effects of psychedelics in perception ( Nichols 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…The details of the image depend on the network weights (which we can interpret as endogenous prior information), the input of style in each layer (which can be interpreted either as endogenous, for imagination, or exogenous for perception) and, to a lesser extent, to noise input. That noise input may be interpreted as spontaneous activity in visual areas such as V1, as it was shown that in mice 5-HT2a receptors are involved in ‘powerful scaling of ongoing and evoked components of population activity in V1’ ( Azimi et al 2020 ), which may thus regulate indirectly the exogenous influence on perception.…”
Section: Nvidia’s Face Generator With Noise Perturbations As a Modelmentioning
confidence: 99%
See 1 more Smart Citation